UMP Facelift Program to beautify Kuala Pahang - UMP, PNC (2017)
Universiti Malaysia Pahang (UMP) organized Gotong Royong Perdana@Facelift D'Kuala to repair the villager’s houses located at the entrance to the Medan Ikan Bakar Complex in Kuala Pahang Village. The program was attended by Peramu Jaya Legislative Assembly, Dato 'Sri Sh Mohmed Puzi Sh Ali and UMP Vice-Chancellor, Dato’ Dr. Daing Nasir Ibrahim together with UMP's top management and Kuala Pahang district head, Hassan Mohamed Sukor.